KNOWLEDGE AND READINESS OF ADOLESCENTS AS PROSPECTIVE BRIDES AND GROOMS IN STUNTING PREVENTION EFFORTS - Hartati, Suryani; Mardhika, Amellia; Dwi Retnani, Ajeng (Universitas Airlangga, 2024)
Introduction: Stunting is currently happening and is a threat to Indonesia. Planning is needed starting from adolescence, having good knowledge and readiness regarding how to prevent having stunted offspring. The target of the Sustainable Development Goals (SDGs) in 2030 includes the second goal, eliminating hunger and all forms of malnutrition and achieving food security, reducing stunting rates by 40% by 2025. The purpose of this study is to analyze the level of knowledge and readiness of adolescents to become prospective brides in an efforts to prevent stunting. Methods: This study uses a survey research design with a sample size of 67 adolescents taken in two cities, DKI Jakarta and Surabaya in 2024. This sampling used purposive sampling. The research variables consist of the knowledge and readiness of adolescents as prospective brides and grooms in efforts to prevent stunting. The instrument used was a questionnaire distributed via Google form distributed by researchers in both areas. The data collected used Spearman rank correlation analysis. Results: There is a relationship between knowledge and the readiness of prospective adolescent brides in efforts to prevent stunting (p=0.001). Conclusions: Health education on stunting, nutritional status, and reproductive health during adolescence must be a mutually supportive program between the Ministry of Health and the Ministry of Education and Culture, both in schools and in integrated “posyandu” that also involve families.